2015
DOI: 10.1017/s0954394514000209
|View full text |Cite
|
Sign up to set email alerts
|

finishvariation and grammaticalization in a signed language: How far down this well-trodden pathway is Auslan (Australian Sign Language)?

Abstract: Language variation is often symptomatic of ongoing historical change, including grammaticalization. Signed languages lack detailed historical records and a written literature, so tracking grammaticalization in these languages is problematic. Grammaticalization can, however, also be observed synchronically through the comparison of data on variant word forms and multiword constructions in particular contexts and in different dialects and registers. In this paper, we report an investigation of language change an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…While this route may be justified for some linguistic aspects, for example grammatical elements (e.g. Pfau & Steinbach 2011;Senghas & Coppola 2011;Johnston et al 2015;Pfau 2015; but see Safar 2020), the fundamental idea is nurtured by reducing variation to optimally low variation (without taking into account the ecological niche of the particular language). Macro-community sign languages, however, may previously have escaped this pressure and are, now characterised as established, analysed on different grounds.…”
Section: Variation and Conventionalisationmentioning
confidence: 99%
“…While this route may be justified for some linguistic aspects, for example grammatical elements (e.g. Pfau & Steinbach 2011;Senghas & Coppola 2011;Johnston et al 2015;Pfau 2015; but see Safar 2020), the fundamental idea is nurtured by reducing variation to optimally low variation (without taking into account the ecological niche of the particular language). Macro-community sign languages, however, may previously have escaped this pressure and are, now characterised as established, analysed on different grounds.…”
Section: Variation and Conventionalisationmentioning
confidence: 99%
“…They found that in their sample, verbs were mouthed 28% of the time and nouns were mouthed 78% of the time. Other studies, such as Bank et al (2015) , Johnston et al (2015) , Rentelis (2011) , and Boyes Braem and Sutton-Spence (2001) similarly found a much higher frequency of mouthing with nouns compared with verbs. This may be at least in part because nouns are generally less morphologically complex than verbs in sign languages (cf.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, the role of a particular token cannot be directly inferred based on its ID gloss ( Johnston, 2012 ). In addition, the sequence of the signs in an utterance is not a reliable indicator because sign languages generally have a relatively flexible constituent order ( Johnston et al, 2015 ). Therefore, we adopted a statistical approach, using the frequency with which a particular ID gloss had been identified as a verb in the parts of the corpus that were already tagged for grammatical category (as part of annotation for the study reported in Fenlon et al, 2018 ) as a starting point.…”
Section: Methodsmentioning
confidence: 99%
“…This is a type of aspect marking which represents an increase in morphological complexity (a similar mouth gesture has been identified in other sign languages, although it does not appear to have the same grammatical role). Perfective aspect marking in ASL, BSL, and Auslan, however, involves the grammaticalization of a manual lexical verb sign meaning ‘finish’ (e.g., Johnston et al, 2015 ). Therefore, it may be the case that micro-community sign languages provide more dense, stable environments compared to macro-community sign languages, and it is here that we might see some emergent complexification, but more detailed investigation needs to be undertaken.…”
Section: Morphological Complexity In Village Sign Languagesmentioning
confidence: 99%